2017
DOI: 10.1088/1361-6455/aa7d2d
|View full text |Cite
|
Sign up to set email alerts
|

Interference-encoded photoionization time delays in the hydrogen atom

Abstract: We present the observation of a checkerboard-like interference pattern in transverse momentum distributions measured for near-threshold photoionization of hydrogen atoms in a DC electric field. We analyze the pattern in terms of constructive and destructive interference between electron trajectories that directly leave the vicinity of the ion and indirect trajectories that remain in the vicinity of the ion for one or more orbital periods, and show that the interference pattern can be discussed in terms of ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…In fact, it is expected that the direct contribution will form a strong fringe system that will be modulated by the indirect one. Indeed, this modulation was experimentally observed recently in hydrogen atom [17] and the modulated beating pattern is found to have the form of a checkerboard structure. This structure is also evident in both maps of Figure 2, for the energy range, -0.5<ε<-0.1.…”
Section: Results and Discusionmentioning
confidence: 53%
See 3 more Smart Citations
“…In fact, it is expected that the direct contribution will form a strong fringe system that will be modulated by the indirect one. Indeed, this modulation was experimentally observed recently in hydrogen atom [17] and the modulated beating pattern is found to have the form of a checkerboard structure. This structure is also evident in both maps of Figure 2, for the energy range, -0.5<ε<-0.1.…”
Section: Results and Discusionmentioning
confidence: 53%
“…Recently these magnitude oscillations were connected to time delays between pairs of electron trajectories, by using the Eisenbud-Wigner time delay definition [23]. Our Mg results imply that the time delay extraction along the lines suggested in [17] may be applicable to the multielectron case as well 050004-5…”
Section: Results and Discusionmentioning
confidence: 59%
See 2 more Smart Citations
“…This phenomenology is nowadays suitably studied by photoionization microscopy (PM) [ 1 ], the term denoting a high-resolution experimental technique where the two-dimensional flux of slow (meV) photoelectrons is imaged by a position sensitive detector (PSD). In a first attempt towards the categorization and classification of the above-mentioned phenomenology, photoionization was described in terms of classical particle scattering in conjunction with the source-to-detector trajectories followed by the electrons under the action of the field [ 1,2,3,4,5,6 ]. These studies revealed that the classical differential photoionization cross section exhibits divergences leading to critical scattering effects such as the so-called rainbow and glory scattering [ 7,8,9 ].…”
Section: Introductionmentioning
confidence: 99%